YOU and YOUR CREDIT: Home Ownership and Credit - Michael S. Gutter; Joan P. Elmore; Travis P. Mountain (EDIS)
This document is FCS7234, part of the YOU and YOUR CREDIT series by Michael S. Gutter, Joan P. Elmore, and Travis P. Mountain. Published by the UF Department of Family Youth and Community Sciences, September 2008.